Ecclesio-Mariological Interpretation of Rev 12:1–6 in Early Christian Writings - Czyżewski, Bogdan (Verbum Vitae, 2023)
Early Christian literature contains numerous commentaries on the books of the Holy Scripture, including the Revelation of St. John. Among the many symbols it contains, we can find an intriguing theme related to the sign of a Woman clothed with the sun (cf. Rev 12:1–6). Nowadays, the above-mentioned passage is most often interpreted in the Mariological spirit. An ecclesiological explanation is provided frequently too. It turns out that in the writings of the early Church authors, the reference to the Church was decidedly the dominant one, while the interpretation favoring Mary was almost marginal. A mixed interpretation was formulated too, for example, by Quodvultdeus. It features three images: ecclesial, Christological, and Mariological. This paper will present the statements made by early Christian authors, representing both the Eastern and the Western Church, on the meaning of the sign of the Woman in the Revelation, and on the ways they interpreted it in commentaries on this book of the Bible.